AI-Assisted Scientific Writing Training to Enhance the Professional Competence of Madrasah Teachers - Sita Nurmasitah; Adhi Kusumastuti; Samsudin Anis; Aryo Baskoro Utomo; Godham Eko Saputro (Universitas Negeri Semarang, 2025)
The AI-assisted scientific writing training was implemented as a community service program to enhance the professional competence of madrasah teachers in the digital era. This activity aimed to equip teachers with the skills to write scientific articles, classroom action research reports, and best practice papers using artificial intelligence (AI) applications such as ChatGPT, Grammarly, QuillBot, and Mendeley. The training was conducted through hands-on practice and online mentoring using an experiential learning approach that emphasized real-world writing experiences. A total of 30 madrasah teachers participated in the program, which consisted of a pre-test, training sessions, writing practice, and a post-test. The results showed an average score improvement of 37%, particularly in aspects of writing structure, paragraph cohesion, academic language use, and reference management. Participants also demonstrated high enthusiasm and began developing independent scientific works for publication purposes. This activity proved that AI-based writing training effectively enhances teachers’ academic productivity and strengthens digital literacy as part of continuous professional development.